PERBANDINGAN KEMAMPUAN MEMBACA SISWA SMA BERPOLA ASUH OTORITER DAN DEMOKRATIS ANTARA YANG DIAJAR DENGAN MODEL SQ3R DAN PQRST - Khabib Sholeh (Kajian Linguistik dan Sastra, 2005)
Coventional technique of reading is commonly used by Senior Hugh School Students that this may due to their low interest and achievement in reading. However, there are more effective reading-techniques such as SQ3R and PQRST and also another factor influencing students'achievement, family-learning way model. The study presents a comparison between reading ability for Seniro High School students using authoritative and democratic way, being taught by using SQ3R and PQRST models. It is an experimental study using students of SMA N 5 Purworejo by factorial design. For the experiment, we selected two classes consisting of the class X-1 as the first experiment group while the class X-2 as the second one. Based on family-learning way model, each group of experiment is devided into two sub-groups, the one getting authoritative while the other getting democratic treatment. The result shows that (1) reading ability of Senior High School students using authoritative family-learning who are taught using SQ3R model, is better than those being taught by using PQRST; (2) reading ability of Senior High School students using democratic way who are taught by using PQRST model, is better than those being taught by using SQ3R; and (3) there is interaction between reading technique using family-learning way model and the students' achievement. In short, technique of reading using family-learning way model has influenced students' achievement of reading.Key words: achievement, family-learning model, authoritative, SQ3R, and PQRST